Occupational Hazards in Corrections: The Impact of Violence and Suicide Exposures on Officers’ Emotional and Psychological Health - St. Louis, Stacie (Criminal justice and behavior, 2023)
Correction officers work in an occupational context where they are often exposed to violence; however, prior research assessing the relationship between violence exposure and officers’ mental health has been limited. The current study sought to better understand the impact of direct and indirect exposure to violence and suicide on psychological health outcomes. Analyzing data from a random sample of 317 correction officers in Massachusetts, findings indicate that personally knowing other officers who died by suicide is associated with greater anger, anxiety, depression, and post-traumatic stress disorder (PTSD). Increased strain-based work–family conflict and departmental discipline were also associated with elevated symptomatology. However, other types of violence exposures, including being assaulted, witnessing staff assaults, and suicides among the incarcerated population, did not predict any outcomes. Furthermore, family support did not serve as a stress buffer for officers exposed to violence, but higher levels of family support were associated with decreased PTSD.